PROSPEK PIDANA KERJA SOSIAL DI INDONESIA - Rukmi, Shinta (Wacana Hukum, 2008)
Abstract   : Community Service order is a new criminal, and it is a rehabilitation to narapidana. The aim of this pidana is to free terpidana from guilty feelings and the community play an active role so the terpidana can do many useful things. Key word  : Punishment.